Fatigue crack propagation experiment and numerical simulation of 42CrMo steel. (July 2020) - Dong, Jianwei; Pei, Weichi; Ji, Hongchao; Long, Haiyang; Fu, Xiaobin; Duan, Hailong
42CrMo steel is widely used in ultrahigh-strength structures such as low-speed heavy-duty gears. Mastering the fatigue crack propagation law has important significance for predicting structural fatigue life. Firstly, the fatigue crack propagation experiment is used to obtain the upper and lower thresholds value of type I fatigue crack propagation of 42CrMo steel compact tensile specimen under the alternating load of stress ratio R = 0.1. The Paris formula describing the relationship between the fatigue crack propagation rate and the crack tip stress intensity factor between the upper and lower thresholds value is obtained. Scanning electron microscopy was used to observe the microscopic features of different stages of fatigue fracture. The results show that the twin boundary can provide a place for crack initiation; the defects in the material can promote the initiation and extension of fatigue cracks. The fatigue crack propagation of 42CrMo steel compact tensile specimens was numerically simulated by the finite element method. The relationship between the crack tip stress intensity factor and the crack length was obtained. The analysis results show that the crack tip stress intensity factor calculated by the plane finite element method differs slightly from the experimental results during the stable extension stage. After correction, the correlation coefficient between the numerical simulation correction value and the crack tip stress intensity factor value obtained by the experiment is 0.9926. Finally, the fatigue crack propagation rate corresponding to the crack tip stress intensity factor in the finite element results is calculated by the Paris formula and briefly analyzed. Compared with the experimental results, it shows that the numerical simulation is consistent with it, indicating the accuracy of the numerical simulation method, which can effectively predict the initiation and propagation of fatigue cracks in 42CrMo steel compact tensile specimens.